PEMBATALAN PERJANJIAN PERKAWINAN SECARA SEPIHAK - Haryanti, Yanti (Institut Nahdlatul Ulama Tasikmalaya, 2024)
Agreement is one of the essential elements of a valid contract and may be annulled if certain conditions stipulated in the Civil Code are met. This study aims to analyze how unilateral contract annulment occurs and its legal consequences. The research employs a normative juridical method, focusing on the internal aspects of positive law by examining literature or secondary data. The method aims to understand, analyze, and interpret the applicable legal norms. An agreement in a contract reflects the mutual consent of two or more parties regarding what they wish to accomplish, how it should be carried out, when it should be executed, and who is responsible for its execution. The conditions for contract annulment are regulated under Article 1266 of the Civil Code, which states that for a contract to be annulled by one party, it must meet the following requirements: the agreement must be reciprocal, there must be a breach of contract (broken promise), and annulment must be requested through the court. If these conditions are not met, the annulment is deemed to violate the law, specifically Article 1266 of the Civil Code. Furthermore, if the annulment contains elements of arbitrariness or exploits the weaker position of the opposing party, it constitutes an unlawful act as it breaches the legal obligation to act in good faith in contractual agreements.